2018
DOI: 10.31031/amms.2018.01.000506
|View full text |Cite
|
Sign up to set email alerts
|

Portable X-Ray Fluorescence Spectrometry: Principles and Applications for Analysis of Mineralogical and Environmental Materials

Abstract: Portable X-ray Fluorescence (pXRF) is a non-destructive compositional analysis technique, which allows the measurement in field, requiring minimum to no sample preparation. This mini-review presents the physical principles and examples of applications of pXRF for the analysis of mineralogical and environmental samples, such as rocks, soils and sediments. All examples described are from the present decade, in order to show some interesting aspect regarding elemental determination capability, result analysis, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…X-ray fluorescence (XRF) is a non-destructive compositional analysis and an emission spectroscopic technique which is based on the interaction of X-rays photons with material [89] . Each X-ray photon has a unique wavelength that can determine the concentrations of different elements present in the matter [89,90,91] . This qualitive and quantitative analytical technique is widely used in various fields and can provide information on material composition [91] .…”
Section: Energy Dispersive X-ray Fluorescencementioning
confidence: 99%
“…X-ray fluorescence (XRF) is a non-destructive compositional analysis and an emission spectroscopic technique which is based on the interaction of X-rays photons with material [89] . Each X-ray photon has a unique wavelength that can determine the concentrations of different elements present in the matter [89,90,91] . This qualitive and quantitative analytical technique is widely used in various fields and can provide information on material composition [91] .…”
Section: Energy Dispersive X-ray Fluorescencementioning
confidence: 99%
“…2.2.1. On-Site Analytical Technologies Used in the Different Case Studies pXRF Among currently available technologies for sediments, portable X-ray fluorescence (pXRF) is one of the best known, and its operation is straightforward [18][19][20]. It allows routine measurements for most of the major elements (Ca, Fe, K, Ti, Mn, and, often with lesser accuracy or higher deviation, Si, Al, P, S and Cl) and for many trace elements (often contaminants: Pb, Zn, Cu, As, Sb, Cr, V, etc).…”
Section: On-site Analytical Technologiesmentioning
confidence: 99%
“…However, Roman Alday et al [16] found that for samples from the Elatsite porphyry-type deposit, pXRF overestimates Fe and K, and underestimates Mg compared to more intensive laboratory methods. Matrix effects on pXRF vary with mineral assemblages and development of calibration standards is reliant on rock type [23,31]. The poorest correlation of the chalcophile elements is for Mo.…”
Section: Causes Of Poor Correlationmentioning
confidence: 99%